2013
DOI: 10.1007/s12035-013-8433-7
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2 and Metalloproteinase-9 Activities are Associated with Blood–Brain Barrier Dysfunction in an Animal Model of Severe Sepsis

Abstract: There is no description on the mechanisms associated with blood-brain barrier (BBB) disruption during sepsis development. Thus, we here determined changes in permeability of the BBB in an animal model of severe sepsis and the role of matrix metalloproteinase (MMP)-2 and MMP-9 in the dysfunction of the BBB. Sepsis was induced in Wistar rats by cecal ligation and perforation. BBB permeability was assessed using the Evans blue dye method. The content of MMP-2 and MMP-9 in the cerebral microvessels was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 37 publications
4
70
0
2
Order By: Relevance
“…We had demonstrated previously that the control of acute inflammation was associated with improved long-term outcome in the CLP model of sepsis (45)(46)(47). Here we demonstrated that the downregulation of CD40 signaling was able to improve long-term cognitive function in sepsis survivor rats.…”
Section: Discussionsupporting
confidence: 55%
“…We had demonstrated previously that the control of acute inflammation was associated with improved long-term outcome in the CLP model of sepsis (45)(46)(47). Here we demonstrated that the downregulation of CD40 signaling was able to improve long-term cognitive function in sepsis survivor rats.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, previous reports have demonstrated that the dysfunction of the BBB followed the development of diseases is temporally related to the increase in MMP-9 [54,55]. It is also intriguing that specific MMP-9 inhibitors ameliorate BBB dysfunction and inflammatory responses [54]. Therefore, we examined whether the changes in MMP-9 activity after Hcy injection induce memory impairments.…”
Section: Discussionmentioning
confidence: 94%
“…These findings suggest that HHcy increases oxidative stress, which results in enhanced levels of MMP-9 that are associated with the loss of memory. Interestingly, previous reports have demonstrated that the dysfunction of the BBB followed the development of diseases is temporally related to the increase in MMP-9 [54,55]. It is also intriguing that specific MMP-9 inhibitors ameliorate BBB dysfunction and inflammatory responses [54].…”
Section: Discussionmentioning
confidence: 99%
“…26 In addition, BBB dysfunction induced by metalloproteinase (MMP) activation was also associated with brain inflammation and cognitive impairment in an animal model of sepsis. 55 This is supported by the fact that MMP-9 content was associated with delirium in the general ICU patient. 44 It is supposed that systemic inflammation can lead to neuronal or glial damage; however, at least in experimental endotoxemia in humans, there is no correlation between acute systemic inflammation and plasma levels of brain specific proteins (S-100b, neuronal enolase [NSE], glial fibrillary acidic protein [GFAP]) nor deterioration of cognitive function.…”
Section: Introductionmentioning
confidence: 86%